2014
DOI: 10.2753/ree1540-496x5004s404
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Credit Cycle and Business Cycle with a Focus on Ten States from Central, Eastern, and Southeastern Europe

Abstract: By performing an econometric analysis of the credit cycle and business cycle from an individual as well as a comparative perspective, with a focus on ten relevant economies from the areas of Central, Eastern, and Southeastern Europe, this research offers a fresh view regarding the importance of banks in promoting long-term economic growth through their lending capacity. The purpose is to better understand the behavior (the short-and medium-term dynamics) of the credit cycle and business cycle and the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…However, Wälti (2009) using probit regressions of synchronicity found that although the introduction of the euro has raised the likelihood of business cycle synchronicity, it has not affected the relative amplitude of business cycles. Apostoaie et al (2014) evaluated credit cycle -business cycle relationship within the synchronicity perspective of ten states from Central, East and Southeast Europe suggesting that banking sectors should not be overregulated for it limits their lending capacity. Crowley and Schultz (2010) by measuring topological differences between GDP growth pattern in recurrence plots for individual countries concluded that there are certain periods of time when growth rate synchronicity increased and these appear to be during the "new" EMS period after 1983 up until roughly 1990, and then again from 1997 through until 2002.…”
Section: Business Cycles Synchronization and Growth Perspectivesmentioning
confidence: 99%
“…However, Wälti (2009) using probit regressions of synchronicity found that although the introduction of the euro has raised the likelihood of business cycle synchronicity, it has not affected the relative amplitude of business cycles. Apostoaie et al (2014) evaluated credit cycle -business cycle relationship within the synchronicity perspective of ten states from Central, East and Southeast Europe suggesting that banking sectors should not be overregulated for it limits their lending capacity. Crowley and Schultz (2010) by measuring topological differences between GDP growth pattern in recurrence plots for individual countries concluded that there are certain periods of time when growth rate synchronicity increased and these appear to be during the "new" EMS period after 1983 up until roughly 1990, and then again from 1997 through until 2002.…”
Section: Business Cycles Synchronization and Growth Perspectivesmentioning
confidence: 99%
“…Examining the determinants of domestic credit, Gueorguiev et al (2005) conclude that capital flows help drive credit growth in Ukraine, while Égert et al (2007) show that GDP per capita plays a role in eight CEE countries, and Allegret and Sallenave (2015) examine capital inflows and credit "booms" in nine CEE economies. Domestic credit can also serve as an explanatory variable in these models: Lane and Milesi-Ferretti (2010) find that both current account deficits and the ratio of private credit to GDP helped explain the intensity of the 2008 crisis in the region, and Apostoaie et al (2014) examine correlations and Granger causality to find linkages between domestic credit and economic growth in Poland and Romania. In one of the few studies that evaluate multiple countries individually, Hegerty (2009) conducts a Vector Autoregression (VAR) analysis of the fixed-rate regimes of Bulgaria and the Baltics and finds that capital inflows drive credit growth only in Bulgaria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3 Buncic and Melecky 2013 discuss the issue of an optimal rate of crediting that does not lead to excessive accumulation of credit risk and credit bubbles-see also references therein. Also, Apostoaie et al 2014 caution the policymakers in emerging markets economies not to overregulate financial markets and strike the right balance between financial development and stability. 4 Beck and De Jonghe 2013; Arcand, Berkes, and Panizza 2012;Pagano 2012;Loayza and Ranciere 2006.…”
Section: Introductionmentioning
confidence: 99%